Odpowiedź :
-8x + 2y = 13
3x - y = 6 / * 2
-8x + 2y = 13
6x - 2y = 12
___________
-2x =1 / :(-2)
3x - y = 6
x = -0,5
3*(-0,5) - y = 6
x = -0,5
-1,5 -y = 6
x = -0,5
-y = 6+1,5 / : (-1)
x = -0,5
y = -7,5
3x - y = 6 / * 2
-8x + 2y = 13
6x - 2y = 12
___________
-2x =1 / :(-2)
3x - y = 6
x = -0,5
3*(-0,5) - y = 6
x = -0,5
-1,5 -y = 6
x = -0,5
-y = 6+1,5 / : (-1)
x = -0,5
y = -7,5
-8x + 2y = 13
3x - y = 6/*2
-8x + 2y = 13
6x -2y=12
-2x=25/:(-2)
x= -12,5
2y= 13+ 8*(-12.5)
2y= 13-100
2y=-87/:2
y=-43,5
3x - y = 6/*2
-8x + 2y = 13
6x -2y=12
-2x=25/:(-2)
x= -12,5
2y= 13+ 8*(-12.5)
2y= 13-100
2y=-87/:2
y=-43,5